Synthesis of Imidazo[1,5-a]quinolines via Metal-Free Oxidative Amination of sp3 C–H Bonds - Liu, Huanhuan; Wang, Xinfeng; Ma, Chen (Synthesis, 2018)
A novel oxidative amination of sp3 C–H bonds was developed for the efficient synthesis of imidazo[1,5-a]quinolines from readily available α-amino acids and (2-azaaryl)methanes. This domino protocol, which was established in a TBAI-TBHP oxidation system, includes transition-metal-free decarboxylation and intramolecular cyclization. This method represented a new avenue for the synthesis of N-heterocycles using 2-methylquinolines as the synthon of quinoline-2-carbaldehydes.
Keywords: quinolone; amino acid; metal-free; oxidative amination; C–H functionalization